Nilai Moral dalam Mitos-Mitos di Kecamatan Katingan Tengah dan Implikasinya Terhadap Pembelajaran Bahasa dan Sastra Indonesia di SMA - Tepi Kaesih; Lazarus Linarto; Alifiah Nurachmana; Linggua Sanjaya Usop; Zainal Arifin; Yuliana Fitri (Universitas Palan, 2023)
This research aims to describe (1) Moral values ​​in myths in Central Katingan sub-district. (2) People's views on moral values ​​in myths in Central Katingan sub-district. (3) The implications of moral values ​​in myths in Central Katingan sub-district for learning Indonesian language and literature in high school. This research uses qualitative descriptive research which is defined as Moral Values ​​in Myths in Katingan Tengah District and Their Implications for Learning Indonesian Language and Literature in High School. In collecting data, this research used observation, interviews and documentation methods. Meanwhile, the steps for this data analysis technique are data collection, data reduction, data presentation and drawing conclusions/verification. As a result of this research, the author found that there were (1) 18 total data from myths consisting of 7 myths about human relationships with their personal lives, while there were 2 myths between humans and other humans, and there were 8 myths about human relationships with God. Moral values ​​actually teach us to maintain good manners and behavior, words and deeds wherever we are and with this myth we respect each other. Therefore, the underlying belief system means that an analysis is needed to be able to answer the aim of this research, namely to describe the belief system that underlies the customs and customs of a belief or myth. Basically, the moral values ​​in myths teach us about politeness, behavior, and respect for cultural customs that apply to religious life (2) Views about myths are the result of human thoughts related to human lives at that time, then they believe these thoughts as outlook on life in meeting their non-physical (thought) needs. (3) The results of this research are used and have implications for class Retell the contents of folk tales (hikayat) that have been heard and read.